1965
DOI: 10.1111/j.1537-2995.1965.tb02923.x
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Transmitting Toxoplasmosis by Blood Transfusion

Abstract: Forty‐three patients with thalassemia major who had received 4,805 transfusions were subjected to the dye test for toxoplasma antibodies. Only three (7%) were found to have subclinical toxoplasmosis, a rate of infection that is within the expected rate for this age group. This study, therefore, provides no evidence that toxoplasmosis was transmitted by transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

1967
1967
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…It is only in these latter that a transfusion effect could produce a spurious result. An examination of the clinical and blood bank records for these patients revealed that, although 12 of the 14 cases had received transfusions for surgery, in only five of these were the dye-tests performed on blood samples drawn after such transfusion at intervals varying from one to 54 days. However, in three of the five the dye-test titers in the cases were of such a magnitude as to require preposterously high titers in the donor (1:170 to 1:1920) to produce them.…”
Section: Discussionmentioning
confidence: 99%
“…It is only in these latter that a transfusion effect could produce a spurious result. An examination of the clinical and blood bank records for these patients revealed that, although 12 of the 14 cases had received transfusions for surgery, in only five of these were the dye-tests performed on blood samples drawn after such transfusion at intervals varying from one to 54 days. However, in three of the five the dye-test titers in the cases were of such a magnitude as to require preposterously high titers in the donor (1:170 to 1:1920) to produce them.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 5 6 ] Toxoplasma pneumonia occurs by respiratory route, transplacental route responsible for abortion and neonatal pathology, nosocomial through blood-transfusion, organ transplants, and laboratory accidents. [ 7 8 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…The disease has a favourable outcome in almost all immunocompetent individuals, whereas it can be life threatening in those who are immunocompromised, such as organ-transplant patients [1]. In the latter setting, the disease can result from T. gondii transmission either within the allograft from a seropositive donor into a seronegative recipient [2–4] or via blood [5] from immunocompetent donors. In organ-transplant recipients, the most usual mechanism is the reactivation of latent infection in the recipient [1].…”
mentioning
confidence: 99%